1990
DOI: 10.1002/1097-4679(199011)46:6<803::aid-jclp2270460619>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of MMPI profile types with corresponding estimated MMPI-2 profiles

Abstract: Changes in mean elevation, dispersion, overall configuration, and code type of well‐defined MMPI profiles were examined after transformation to estimated MMPI‐2 profiles. A total of 34 MMPI profiles from both Gilberstadt and Duker (1965) and Marks, Seeman, and Haller (1974) were analyzed using contemporary MMPI‐2 T‐scores. Results yielded a reduction in mean elevation and both increases and decreases in scatter about the mean upon transformation to MMPI‐2 norms. The total configuration of linear MMPI and estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The K-corrected T scores on the clinical scales of the MMPI-2 and the revised MacAndrew's Alcoholism Scale (MAC-R) were the dependent variables in all analyses. The original MMPI was restandardized in 1989, which resulted in the MMPI-2; several studies have demonstrated the comparability of the MMPI and MMPI-2 (Levitt, 1990;Munley & Zarantonello, 1990). Of most relevance to the present study is the fact that the comparability of the MMPI and the MMPI-2 has been demonstrated specifically in a college student sample (Ben-Porath & Butcher, 1989).…”
Section: Dependent Measuresmentioning
confidence: 79%
“…The K-corrected T scores on the clinical scales of the MMPI-2 and the revised MacAndrew's Alcoholism Scale (MAC-R) were the dependent variables in all analyses. The original MMPI was restandardized in 1989, which resulted in the MMPI-2; several studies have demonstrated the comparability of the MMPI and MMPI-2 (Levitt, 1990;Munley & Zarantonello, 1990). Of most relevance to the present study is the fact that the comparability of the MMPI and the MMPI-2 has been demonstrated specifically in a college student sample (Ben-Porath & Butcher, 1989).…”
Section: Dependent Measuresmentioning
confidence: 79%
“…Third, the profile changes resulting from the new norms are complex (Munley, 1991a; Ward, 1991). Munley and Zarantonello (1990) and Vincent (1990) also analyzed the comparative data within the manual. It appeared that the bulk of the changes in profile code types resulted from the new norms and not the change to uniform T scores (Graham, Timbrook, Ben-Porath, & Butcher, 1991).…”
Section: Major Structural Problemsmentioning
confidence: 99%
“…MMPI reliability coefficients for the Basic scales ranged from .60 to .95. Munley and Zarantonello (1990) used this model in considering profile changes for classic MMPI profiles on transformation to MMPI-2 norms; however, the model has apparently not yet been used as a frame of reference for considering MMPI or MMPI-2 profile configurations over time. Test-retest agreement for high-point and twopoint codes was 42.72% and 27.65%, respectively.…”
mentioning
confidence: 99%